Lung stress, strain, and energy load: engineering concepts to understand the mechanism of ventilator-induced lung injury (VILI) - Nieman, Gary F. (Intensive Care Med Exp, 2016)
It was recently shown that acute respiratory distress syndrome (ARDS) mortality has not been reduced in over 15 years and remains ~40 %, even with protective low tidal volume (LVt) ventilation. Thus, there is a critical need to develop novel ventilation strategies that will protect the lung and reduce ARDS mortality. Protti et al. have begun to analyze the impact of mechanical ventilation on lung tissue using engineering methods in normal pigs ventilated for 54 h. They used these methods to assess the impact of a mechanical breath on dynamic and static global lung strain and energy load. Strain is the change in lung volume in response to an applied stress (i.e., Tidal Volume-Vt). This study has yielded a number of exciting new concepts including the following: (1) Individual mechanical breath parameters (e.g., Vt or Plateau Pressure) are not directly correlated with VILI but rather any combination of parameters that subject the lung to excessive dynamic strain and energy/power load will cause VILI; (2) all strain is not equal; dynamic strain resulting in a dynamic energy load (i.e., kinetic energy) is more damaging to lung tissue than static strain and energy load (i.e., potential energy); and (3) a critical consideration is not just the size of the Vt but the size of the lung that is being ventilated by this Vt. This key concept merits attention since our current protective ventilation strategies are fixated on the priority of keeping the Vt low. If the lung is fully inflated, a large Vt is not necessarily injurious. In conclusion, using engineering concepts to analyze the impact of the mechanical breath on the lung is a novel new approach to investigate VILI mechanisms and to help design the optimally protective breath. Data generated using these methods have challenged some of the current dogma surrounding the mechanisms of VILI and of the components in the mechanical breath necessary for lung protection.